1995
DOI: 10.2307/30140998
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Pseudomonas cepacia and Other Pseudomonas Species from the Environment

Abstract: Nine hundred sixteen cultures were obtained from homes of patients with cystic fibrosis, control homes, salad bars, and food markets, and analyzed for the presence of Pseudomonas cepacia and related bacteria. P cepacia was recovered from 5 (18%) of 27 homes, and from 20 (4%) of 509 cultures collected outside of homes. Relative to other pseudomonads, P cepacia is found infrequently in the environment. It is not clear how frequently these sources contribute to acquisition of this bacteria by persons with cystic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Finally, while recent reports (14-17) suggest that a common epidemic B. c~ppmciu strain is prevalent in CF centres, our data suggest low contagiousness, at least for some strains, and point to the reservoir of B. cc~pacia outside the hospital as a possible source of B. cepaciu infection in CF patients. This hypothesis is supported by the prevalence in our CF population of patients with unique strains (53.3% for the study period as a whole, and 69.2% 1 year after the adoption of the segregation policy) and by recent observations (17,23).…”
Section: Discussionsupporting
confidence: 75%
“…Finally, while recent reports (14-17) suggest that a common epidemic B. c~ppmciu strain is prevalent in CF centres, our data suggest low contagiousness, at least for some strains, and point to the reservoir of B. cc~pacia outside the hospital as a possible source of B. cepaciu infection in CF patients. This hypothesis is supported by the prevalence in our CF population of patients with unique strains (53.3% for the study period as a whole, and 69.2% 1 year after the adoption of the segregation policy) and by recent observations (17,23).…”
Section: Discussionsupporting
confidence: 75%
“…In particular, although B. multivorans and B. gladioli together account for greater than half of the Burkholderia infections in the CF population, at least in the United States, strains belonging to these two species that are shared by multiple CF patients are uncommon. These observations indicate that the majority of new Burkholderia infection in CF patients currently involves the acquisition of strains from independent sources, most likely in the natural environment (115,210). Indeed, a recent analysis employing multilocus sequence typing (MLST) demonstrated that more than 20% of 381 CF isolates were indistinguishable from strains recovered from the environment (13).…”
Section: Burkholderia Speciesmentioning
confidence: 99%
“…Because implementation of infection control measures has reduced, but not eliminated new acquisition of B. cepacia complex by CF patients, several studies have examined strains recovered from various environmental sources in an attempt to identify possible reservoirs for these species. 231,232 Mortensen et al cultured numerous sites within the homes of 14 CF patients and 13 controls to look for possible reservoirs. 231 B. cepacia complex strains were found in 5 of 916 cultures: 3 from the homes of CF patients and 2 from the homes of controls.…”
Section: Environmental Reservoirs Of B Cepacia Complexmentioning
confidence: 99%